Asymptomatic Meconium Peritonitis Presenting as Inguinal Hernia in a Female Neonate - Sivasankar Jayakumar; Laila Hatsell; Nitin Patwardhan (EL-Med-Pub, 2013)
Inguinal hernias in girls are often irreducible when they contain ovaries. Rarely the hernial sacs may have unusual contents like vermiform appendix, uterus and urinary bladder. We report a case of a female infant who presented with bilateral irreducible inguinal hernias presumed to be due to ovaries. However at exploration, the hernial sacs contained bilaterally an omental mass with calcifications. Presence of mucin with meconium- laden macrophages in the mass on histology suggested an antenatal intestinal perforation. To the best of our knowledge no such case has been reported in a female neonate. We present this rare case and discuss the unusual findings and the outcome.